2011
DOI: 10.1017/s0007114511005769
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-supplemented yoghurt improves physiological and biochemical markers of experimental diabetes

Abstract: We investigated the effects of prolonged treatment of diabetic rats with curcumin-supplemented yoghurt on the physiological and biochemical changes associated with diabetes mellitus. An established metabolic cage model was used to assess these changes in three groups of streptozotocin-diabetic rats which had been administered, by gavage, curcumin blended into yoghurt in the doses of 30, 60 and 90 mg/kg body weight (BW) per d (groups DC 30 , DC 60 , DC 90 ) for 31 d. One group of non-diabetic rats was also trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 40 publications
(41 reference statements)
9
60
0
2
Order By: Relevance
“…Furthermore, curcumin supplemented with vitamin C (Patumraj et al, 2006) and yoghurt (Gutierres et al, 2012) has been shown to be effective in reducing the levels of blood glucose, haemoglobin (Hb) and HbA1c in STZ induced diabetes models. In addition, it can prevent the alterations of blood levels of IL-6, MCP-1, TNF-α, glucose and HbAIC (Giacco and Brownlee, 2010).…”
Section: Effect Of Curcumin On Diabetesmentioning
confidence: 99%
“…Furthermore, curcumin supplemented with vitamin C (Patumraj et al, 2006) and yoghurt (Gutierres et al, 2012) has been shown to be effective in reducing the levels of blood glucose, haemoglobin (Hb) and HbA1c in STZ induced diabetes models. In addition, it can prevent the alterations of blood levels of IL-6, MCP-1, TNF-α, glucose and HbAIC (Giacco and Brownlee, 2010).…”
Section: Effect Of Curcumin On Diabetesmentioning
confidence: 99%
“…Numerous reports have been published suggesting that oral administration of curcumin down-regulates TNF-a expression both in the serum and in the tissue of animals (Nanji et al, 2003;Yao et al, 2004;Sharma et al, 2007a;Billerey-Larmonier et al, 2008;Larmonier et al, 2008;Ung et al, 2010;El-Moselhy et al, 2011;Gutierres et al, 2012) ( Table 2). Attenuation of TNF-a levels by curcumin has been noted in mice (Leyon and Kuttan, 2003), rats (Siddiqui et al, 2006) and rabbits (Yao et al, 2004;Huang et al, 2008).…”
Section: Suppression Of Tnf By Curcumin In Vivomentioning
confidence: 99%
“…Bixin (from Bixa orellana L. seeds) is used as a colorant in a range of cosmetics and foods (butter, cheese, bakery products, oil, cereal, and sausage). A wide range of beneficial effects towards the metabolic disturbances associated with DM has been attributed to these natural antioxidants [19,20,21,22,23], motivating the study of combinations of these antioxidants as a complementary strategy for the prevention of long-term complications of diabetes. There is no data available, as far as we know, about the prospective in vivo benefit of these natural ingredients when used in combination.…”
Section: Introductionmentioning
confidence: 99%